2023
DOI: 10.1021/acsami.2c20986
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Inorganic All-Solid-State Electrochromic Devices toward Visual Energy Storage and Two-Dimensional Color Tunability

Abstract: Multicolor display has gradually become a soughtafter trend for electrochromic devices due to its broadened application scope. Meanwhile, the advantages of inorganic electrochromic devices such as stable electrochemical performance and good energy storage ability also have great attraction in practical production applications. However, there are still huge challenges for inorganic electrochromic materials to achieve multicolor transformation due to their single-color hue change. Herein, we design an inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Both areal capacities showed a decreasing trend as the current density increased due to insufficient reaction at the large current density. 47 Meanwhile, the LTO and LMO films had almost equal capacity ranging from 0.1 to 0.8 mA cm À2 . In conclusion, LMO and LTO films achieved the matched charge storage capabilities and EC behaviors, which promoted the construction of high-performance EC batteries.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Both areal capacities showed a decreasing trend as the current density increased due to insufficient reaction at the large current density. 47 Meanwhile, the LTO and LMO films had almost equal capacity ranging from 0.1 to 0.8 mA cm À2 . In conclusion, LMO and LTO films achieved the matched charge storage capabilities and EC behaviors, which promoted the construction of high-performance EC batteries.…”
Section: Resultsmentioning
confidence: 98%
“…3c, the b values of Peak 1 and Peak 2 were calculated to be 0.36 and 0.35, respectively, which demonstrated that the total capacity of the LTO was mainly controlled by the Li-ions diffusion behavior. 46,47 Here, the area specific capacity was used to evaluate the energy storage performance of the LTO. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6(b)). Ding et al 69 employed MnO 2 film as the counter electrode and Prussian blue film as the working electrode to develop a flexible multicolor EC storage device (Fig. 6(c)).…”
Section: Inorganic Multicolor Electrochromic Devices Based On the Int...mentioning
confidence: 99%
“…16c). 123 During the charging/discharging process, various degrees of yellow, green, and blue corresponded to different energy states. To further expand the range of colors that can be displayed, the combination of WO 3 and SVO electrodes was proposed to display multiple colors traversing a 2D CIE regional color space.…”
Section: Strategies Of Multicolormentioning
confidence: 99%